Seismic retrofit of large-scale interior RC beam-column-slab joints after standard fire using steel haunch system. (1st February 2022) - Cai, Ziwei; Liu, Xin; Wu, Renjun; Li, Lingzhi; Lu, Zhoudao; Yu, Kequan
Highlights: Fire damage and temperature field of RC beam-column-slab joints subjected to the standard fire were analyzed. Steel haunch system enhanced seismic performance of post-fire RC beam-column-slab joints. Steel haunch can be effectively combined with bolted side plates and CFRP sheets. The sequentially coupled thermal-stress numerical analysis was conducted to explore the structural behavior. Abstract: Steel haunch system was proposed to retrofit fire-damaged reinforced concrete (RC) beam-column-slab joints and ensure their seismic safety. Five RC beam-column-slab joints were designed, including one control specimen without fire damage, one control fire-damaged specimen, three fire-damaged specimens retrofitted with different types of steel haunch system, i.e., separate steel haunches, a combination of steel haunches and carbon fiber-reinforced polymer (CFRP) sheets, and a combination of steel haunches and bolted side plates (BSP). The fire-damaged RC joints were subjected to ISO 834 standard fire. After fire tests, low-cycle reversed loading tests were conducted on all the control and retrofitted specimens. The influence of fire damage and retrofit methods on the hysteretic behavior, load capacity, stiffness, ductility factor, and energy dissipation capacity of the joints was analyzed. Experimental results showed that fire exposure significantly reduced the seismic performance of RC beam-column-slab joints. The plastic hinges of spatial joints were transferred from the beam-column interface to the zone outside steel haunches after retrofitting. Compared with the control fire-damaged specimen, the hysteretic curves of the retrofitted specimens were more stable and plumper. All the three strengthening methods effectively enhanced the ultimate load capacity (increased by 24–70%), stiffness, ductility and cumulative hysteresis energy (increased by 107–362%) of the post-fire joints. CFRP sheets and bolted side plates show excellent compatibility with the steel haunches. The preload degradation of bolts used to fix the steel haunches reduced the retrofit efficiency of the steel haunch system. The numerical results of the sequentially coupled thermal-stress analysis model for retrofitted post-fire RC joints based on ABAQUS were consistent with the experimental results.